Florida Crop/Pest Management Profile: Herbs (Basil, Cilantro, Dill, Mint, Parsley, Rosemary, Sage, Thyme) - Mark A. Mossler (EDIS)
Because herbs are vegetative crops, the most important pest groups in Florida production include the early season diseases, weeds, and leaf-feeding insects. Nematodes and viruses are generally not problematic in Florida herb production. This document is PI-65, one of a series of publications of the Pesticide Information Office, Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published November 2005.